Socio-technical networks science and engineering design - Hu, Fei.; Mostashari, Ali.; Xie, Jiang (Boca Raton, Fla. : CRC Press, 2010)
"While there are some sporadic journal articles on socio-technical networks, readers need an integrated resource discussing the STN design. This book provides a complete introduction to the fundamentals of socio-technical networks, including its definition, historical background, and significance. The authors provide basic network architecture from the OSI model perspective and address some challenging design issues. The text also covers all major network protocol design in a typical STN and the application of wireless networks such as sensor networks, WiMAX, etc. in STN access. The book presents STN case studies from healthcare, virtual communities"--
"This book provides a complete introduction to the fundamentals of socio-technical networks, including its definition, historical background, and significance. The authors provide basic network architecture from the OSI model perspective and address some challenging design issues. The text covers all major network protocol design in a typical STN and the application of wireless networks in STN access. The last part presents case studies from healthcare, virtual communities, and power plant management"--
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Computer networks; Command and control systems -- Design; Online social networks -- Design; Information networks -- Design; Electronic books